2007
DOI: 10.1007/s11259-006-3565-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Gentamicin after Intravenous, Intramuscular, Subcutaneous and Oral Administration in Broiler Chickens

Abstract: The pharmacokinetics and bioavailability of gentamicin sulphate (5 mg/kg body weight) were studied in 50 female broiler chickens after single intravenous (i.v.), intramuscular (i.m.), subcutaneous (s.c.) and oral administration. Blood samples were collected at time 0 (pretreatment), and at 5, 15 and 30 min and 1, 2, 4, 6, 8, 12, 24 and 48 h after drug administration. Gentamicin concentrations were determined using a microbiological assay and Bacillus subtillis ATCC 6633 as a test organism. The limit of quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…, 1995). Systemically administered aminoglycosides are much more bioavailable than when given orally (Abu‐Basha et al. , 2007a); therefore, residues are more likely to be found in eggs.…”
mentioning
confidence: 99%
“…, 1995). Systemically administered aminoglycosides are much more bioavailable than when given orally (Abu‐Basha et al. , 2007a); therefore, residues are more likely to be found in eggs.…”
mentioning
confidence: 99%
“…Drug retention in the gastrointestinal tract is advantageous for treating gastrointestinal infections. The result was higher than apramycin in chicken (1.31%) (EL-Sayed et al, 2018) in chicken (2.03%) (Afifi et al, 1997), 2.5 % (Elbadawy & Aboubakr,2017), in Japanese quails 0.56% (Lashev and Mihailov, 1994), in chicken (3.77%) (Lashev, 1998 ), However, the got data was lower than that seen for different species when given by ways other than the oral method such as in calves (61.98%) (EL-Sayed et al, 1994), and in turkey roosters (107.61 ± 33.56%), gentamycin in turkey roosters (97.2 ± 31.41 %) (Haritova et al, 2004, amikacin in lactating ewes (98.27%) (Abo el-Sooud, 1999, amikacin in cats (95± 20%) (Jernigan et al, 1988), gentamycin in chicken (79%) (Abu-Basha et al, 2007), and neomycin in sheep (74-85%) (Errecalde et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…With all precautions necessary, the present study indicates a possible role of oral Gentamycin in treatment of NEC. Oral gentamicin is not absorbed during its passage within the gastrointestinal tract and does not affect calculation and prescription of parenteral antibiotics 18‐20 . In 2020, it was shown that the use of an oral antibiotic for prevention of NEC was found not to be associated with a reduced diversity or reduced abundance of microbiome signatures within the first 2 weeks of life 21 .…”
Section: Discussionmentioning
confidence: 99%
“…16 In 2017, a systematic review of the literature showed that the use of preventive probiotics has significant potential to reduce mortality and morbid- tibiotics. [18][19][20] In 2020, it was shown that the use of an oral antibiotic for prevention of NEC was found not to be associated with a reduced diversity or reduced abundance of microbiome signatures within the first 2 weeks of life. 21 There is always a need for iv antibiotic regimens in the treatment of NEC.…”
Section: Discussionmentioning
confidence: 99%